Renewable saccharide-derived porous carbon foams with metal particles for CNT and graphene substrates in electrochemical applications - Yi Ma; William Coley; Ruoxu Shang; Fabian Villalobos; Pedro Pena; Andrew Patalano; Evan Jauregui; Nicholas Roskopf; Mihrimah Ozkan; Cengiz S. Ozkan (iScience)
Summary: Harnessing the potential of renewable saccharides, porous carbon foams embedded with metal nanoparticles have been innovatively synthesized, pushing the boundaries of electrochemical applications. By embedding metal nanoparticles in carbon foams derived from saccharides and metal salts, substrates for the growth of multi-walled carbon nanotubes (MWCNTs) and multi-layer graphene through chemical vapor deposition (CVD) are created. The influence of varying saccharide-to-metal precursor ratios on the morphology of these nano-structured carbons is examined. The diameters of carbon nanotubes formed at different saccharide to nickel (Ni) ratios are compared, with corroborative insights from X-ray diffraction (XRD) and Raman spectroscopy. Substituting cobalt (Co) salts for Ni precursors reveals notable differences in carbon morphologies. The resulting carbon nanotube-carbon foam composites exhibit remarkable properties, enabling the creation of hierarchical carbon foams. Furthermore, their potential as carbon electrodes for electrochemical double-layer capacitors (EDLCs) is evaluated, highlighting their promise in cutting-edge electrochemical applications.